Draft Genome Sequences of Vibrio alginolyticus Strains V1 and V2, Opportunistic Marine Pathogens - Castillo, Daniel (Genome Announc, 2015)
We announce the draft genome sequences of Vibrio alginolyticus strains V1 and V2, isolated from juvenile Sparus aurata and Dentex dentex, respectively, during outbreaks of vibriosis. The genome sequences are 5,257,950 bp with a G+C content of 44.5% for V. alginolyticus V1 and 5,068,299 bp with a G+C content of 44.8% for strain V2. These genomes provide further insights into the putative virulence factors, prophage carriage, and evolution of this opportunistic marine pathogen.